Building Global Labour Networks: The Case of the Global Labour University - Hoffer, Frank (Just Labour, 2006)
The article discusses the experience of the Global Labour University project. Summarizing major challenges labour is facing in adapting to the structural changes of globalisation, the paper puts the idea of a Global Labour University in the broader context of labour's needs to respond to a dominantly pro-business, pro-market globalisation discourse. The second part of the article introduces and critically discusses the Global Labour University project as an initiative to contribute to the need for global research, teaching and networking for a fairer globalisation.